Modern weapons and military equipment for issue 2/2014 - Tišma, Mladen R. (Vojnotehnički glasnik / Military Technical Courier, 2014)
MiG-41 successor of heavy interceptor MiG-31 Poland extends service life of its Su-22 strike fighters Flight tests of Taurus KEPD 350 integration onto Eurofighter started Boeing maritime surveillence aircraft first flight Taiwan shows upgraded IDF fighter jet India considers licence production of PC-7 Mk II Air Strato UAV first flight First French AWACS completed MLU Radar-equiped Z-19 revealed Second test of Arrow 3 missile interceptor First guided launch of Mizrak-U anti-tank missile AESA equiped Eurofighter to take off this year Russia continiues development of Yak-152 trainer Italian HH-101 helicopter’s first flight Israeli UAV Super Heron HV unveiled US special forces explore gunship-variant V-22